STUDY OF THE MOTIVATION OF THE TEACHERS WHO COORDINATE THE PROJECTS FOR THE EDUCATIONAL INTEGRATION OF THE TIC - Enrique Sánchez Rivas (Publicaciones, 2014)
The complexity of the educational and incriminating dynamic sense and, in turn, attributed to education professionals need to engage in a process of reflection on their actions, a long process aimed at improving educational practice. In this regard, educational research is the basis for understanding and improving educational processes. The research reported in this article aims to increase awareness of the influence of variables such as personal on the development of functions under the coordination of projects incorporating information technology and communication to the teaching and learning in schools public in the province of Malaga. In particular, elaborates on the motivation of teachers engaged in project coordination and analyzes the differences associated with the gender variable.